Modern Problems of Mathematical Modeling, Computational Methods and Information Technologies: (Моделювання, керування та інформаційні технології, 2020)
Modern Problems of Mathematical Modeling, Computational Methods and Information Technologies: Materials of International scientific conference. – Rivne, 2018. – 317 p.